A case-control study of tackle based head impact event (HIE) risk factors from the first three seasons of the National Rugby League Women's competition - McLeod, Shreya; Tucker, Ross; Edwards, Suzi; Jones, Ben; Page, Georgia; Spiegelhalter, Mily; West, Stephen W.; Iverson, Grant L.; Gardner, Andrew J. (Frontiers in Sports and Active Living, 2023)
Objective: The tackle is the most injurious event in rugby league and carries the greatest risk of concussion. This study aims to replicate previous research conducted in professional men’s rugby league by examining the association between selected tackle characteristics and head impact events (HIEs) in women’s professional rugby league. Methods: We reviewed and coded 83 tackles resulting in an HIE and every tackle (6,318 tackles) that did not result in an HIE for three seasons (2018-2020) of the National Rugby League Women’s (NRLW) competition. Tackle height, body position of the tackler and ball carrier, as well as the location of head contact with the other player’s body were evaluated. Propensity of each situation that caused an HIE was calculated as HIEs per 1,000 tackles. Results: The propensity for tacklers to sustain an HIE was 6.60 per 1,000 tackles (95% CI: 4.87-8.92), similar to that of the ball carrier (6.13 per 1,000 tackles, 95% CI: 4.48-8.38). The greatest risk of an HIE to either the tackler or ball carrier occurred when head proximity was above the sternum (21.66 per 1,000 tackles, 95% CI: 16.55-28.35). HIEs were most common following impacts between two heads (287.23 HIEs per 1,000 tackles, 95% CI: 196.98-418.84). The lowest propensity for both tackler (2.65, 95% CI: 0.85-8.20) and ball carrier HIEs (1.77 per 1,000 tackles, 95% CI: 0.44-7.06) occurred when the head was in proximity to the opponent’s shoulder and arm. No body position (upright, bent or unbalanced/ off feet) was associated with an increased propensity of HIE to either tackler or ball carrier. Conclusions: In the NRLW competition, tacklers and ball carriers have a similar risk of sustaining an HIE during a tackle, differing from men’s NRL players, where tacklers have a higher risk of HIEs. Further studies involving larger samples need to validate these findings. However, our results indicate that injury prevention initiatives in women’s rugby league should focus on how the ball carrier engages in contact during the tackle as well as how the tackler executes the tackle.